ANALYSIS INFLUENCE OF HEDONIC SHOPPING TENDENCY ON IMPULSE BUYING WITH POSITIVE EMOTION AS INTERVENING VARIABLE IN THE LADY'S AREA OF THE MATAHARI DEPARTMENT STORE BIM BENGKULU CITY - Syah Rani Augie Safitri; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This study tries to find out what factors cause consumers to make impulse purchases in the women's area at Matahari Department Store Bencoolen Indah Mall. The variables examined in this study include hedonic shopping tendencies and visual merchandising as independent variables, positive emotions as intervening variables, and impulse buying as the dependent variable. The sample used amounted to 100 respondents. By using the PLS-SEM analysis technique, it is shown that through positive emotions, hedonic shopping tendencies and visual merchandising influence impulse purchases.